Social studies discoveries on the net : an integrated approach - Fredericks, Anthony D. (Englewood, CO : Libraries Unlimited, 2000)
Provides resources, activities, and teaching suggestions for more than seventy social studies units involving the Internet.
Includes bibliographical references and index.
Library Talk.
School Library Journal.
Professional
Keywords: Internet in education -- United States; Social sciences -- Study and teaching (Elementary) -- Computer network resources; Social sciences -- Study and teaching (Elementary) -- United States -- Computer network resources; Education -- United States -- Internet resources; Social sciences -- United States -- Study and teaching -- Internet resources